Cultural Heritage or Traces of the War? A Case Study From Oblivion to Memory and ’Heritagisation’ - Marinka, Melinda (Ethnographica et Folkloristica Carpathica, 2020)
The paper explores the memory of the internment camp in Tiszalök (Upper Tisza region, Hungary) in selected social, historical, and ethnic contexts. After a brief theoretical overview of key concepts such as heritagization, the author highlights some significant facts and events from the history of the camp. This camp was established after the Second World War, and deportees of German origin, who could not go home to their families after returning to Hungary from Russian captivity, were held there. Furthermore, the paper outlines how the history of the camp was first concealed in public, then gradually discovered by scholars and memorialized through commemorative events and a monument which was erected by the local community and former inmates. Subsequently, the author presents the case study of a deceased Hungarian woman who used to work in the camp’s kitchen. Based on several interviews with her relatives and after the careful examination of a wooden box from her estate, the author demonstrates that her family history and the history of the interned members of the German minority are closely intertwined in a way, which had been unknown to her family. Finally, the author argues that similar personal objects may reveal further untold stories and entangled memories from the postwar years.